Fat graft survival inside pocket for silicone implant - DURMUŞ KOCAASLAN, FATMA NİHAL; BAYRAMİÇLİ, MEHMET NURİ ÜMİT (MARMARA UNIV, FAC MEDICINE, 2020)
Objective: The aim of this study was to investigate the survival potential of the fat grafts inside the implant capsule in an experimental setting. Materials and Methods: Twenty male Wistar albino rats were used. A two-staged surgical procedure was performed. In the first stage, silicone sheets were placed in the subcutaneous plane on the left side of each rat. On day 60, fat grafts injected into the silicone capsule either by removing the silicone sheaths or leaving the silicone sheaths in their place. In both groups, the same amount of the fat grafts was injected into the right side of the dorsal subcutaneous plane of the rats and they served as their own controls. The findings were evaluated according to the histopathological criteria. Results: There was no statistically significant difference in the inflammatory cell infiltration, fibrosis, and necrotic adipocytes among the groups. Although, the fat viability rate was higher in control groups, there was no statistically significant difference compared to the capsule or silicone groups (p>0.05). Conclusion: Our study results suggest that implant capsule is a hospitable environment and resection of the capsule is unnecessary, if silicone implants are expected to be removed following fat injection.
Keywords: Fat graft; Lipofilling; Adipocyte; Capsule; Silicone implant; Prosthesis; BREAST RECONSTRUCTION; CONTOUR DEFORMITIES; POLYURETHANE FOAM; FIBROUS CAPSULE; SURFACE; TRANSPLANTATION; CONTROVERSIES; INJECTION